The Balanced Scorecard: Strategic Planning and Management - Khan, Imran Ahmad (Prabandhan: Indian Journal of Management, 2012)
The balanced scorecard is a strategic planning and management system used to align business activities to the vision and strategy of the organization, improve internal and external communications and monitor organizational performance against strategic goals. Traditional financial performance metrics provide information about a firm’s past results, but are not well-suited for predicting future performance or for implementing and controlling the firm’s strategic plan. By analyzing perspectives other than the financial one, managers can better translate the organization’s strategy into actionable objectives and better measure how well the strategic plan is executing. The balanced scorecard is a management system that maps an organization’s strategic objectives into performance metrics in four perspectives: financial, internal processes, customers, and learning and growth. These perspectives provide relevant feedback as to how well the strategic plan is executing so that adjustments can be made as necessary.